No two persons eaudiobook - Bauermeister, Erica (Macmillan Audio, 2023)
Winner of the 2024 Audie Award for Multi-voiced Performance! This program includes a bonus conversation between the author and narrator. "The production's 10 outstanding real-life narrators portray the fictional audiobook's author and its nine narrators. Each of the talented real-life narrators brings their character vividly to life."- AudioFile One book. Nine readers. Ten changed lives. New York Times bestselling author Erica Bauermeister's No Two Persons is "a gloriously original celebration of fiction, and the ways it deepens our lives."* That was the beauty of books, wasn't it? They took you places you didn't know you needed to go... Alice has always wanted to be a writer. Her talent is innate, but her stories remain safe and detached, until a devastating event breaks her heart open, and she creates a stunning debut novel. Her words, in turn, find their way to readers, from a teenager hiding her homelessness, to a free diver pushing himself beyond endurance, an artist furious at the world around her, a bookseller in search of love, a widower rent by grief. Each one is drawn into Alice's novel; each one discovers something different that alters their perspective, and presents new pathways forward for their lives. Together, their stories reveal how books can affect us in the most beautiful and unexpected of ways—and how we are all more closely connected to one another than we might think. "With its beautiful parts that add up to a brilliant whole, No Two Persons made my reader's heart sing."—*Nina de Gramont, New York Times bestselling author of The Christie Affair This program is read by a full cast: Rachel Jacobs as The Writer Barrie Kreinik as The Assistant Braden Wright as The Actor Jesse Vilinsky as The Artist Max Meyers as The Diver Gabra Zackman as The Teenager Stephen Graybill as The Bookseller George Newbern as The Caretaker Cassandra Campbell as The Coordinator Carol Jacobanis as The Agent A Macmillan Audio production from St. Martin's Press.